2020
DOI: 10.3390/foods9081085
|View full text |Cite
|
Sign up to set email alerts
|

Sesame, Pistachio, and Macadamia Nut: Development and Validation of New Allergenic Systems for Fast Real-Time PCR Application

Abstract: Food allergy is a worldwide health problem that concerns infants to adults. The main health risk for sensitised individuals is due to the presence of traces of allergens as the result of an accidental contamination during food processing. The labelling of allergens such as sesame, pistachio, and macadamia nut on food products is mandatory according to Regulation (EU) N. 1169/2011; therefore, the development of suitable and specific analytical methodologies is advisable. The aim of this study was to perform a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…For instance, Sanchiz et al [ 34 ] reported that they used “Ara h 6” as a peanut allergen-coding region for the determination of peanut allergens that are impacted by different processing methods. Additionally, Toricelli et al [ 35 ] highlighted the achievements of the 2S albumin gene, performed by real-time PCR, for sesame, pistachio, and macadamia detection in commercial food samples. The allergen-encoding amplification results of the canned tuna groups are given in Figure 1 A.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Sanchiz et al [ 34 ] reported that they used “Ara h 6” as a peanut allergen-coding region for the determination of peanut allergens that are impacted by different processing methods. Additionally, Toricelli et al [ 35 ] highlighted the achievements of the 2S albumin gene, performed by real-time PCR, for sesame, pistachio, and macadamia detection in commercial food samples. The allergen-encoding amplification results of the canned tuna groups are given in Figure 1 A.…”
Section: Resultsmentioning
confidence: 99%
“…MiAMP2 vicilin-like protein accounts for almost 20% of the protein abundance in macadamia . Thus, it is frequently employed for the detection of macadamia residuals. , We therefore aimed to develop a sandwich ELISA detection strategy with the allergen-specific Nbs against vicilin-like proteins of macadamia. Thus, Nbs with His-tag only (as opposed to HA- and His-tag) were generated to serve as the antigen capturing Nbs.…”
Section: Resultsmentioning
confidence: 99%
“…Torricelli et al, designed primers for the vicilin precursor gene as the target to develop a fast real-time PCR. The practical LOD was determined as 0.006% . Ito et al also reported a PCR-based detection technique with a detection limit of 1 pg of macadamia DNA .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations